Mengenal Angka Melalui Media Kartu Angka Pada Anak Usia Dini di RA Nurul Ummi Binjai Baru Kabupaten Batubara - Syahrizal, Syahrizal; Manurung, Ade Karunia Rizky (ALACRITY : Journal of Education, 2024)
Developing various skills of children according to age level and taking into account the characteristics of development, creatively teachers can make and use game tools that come from the surrounding environment and utilize used goods or media that already exist or are available. The formulation of the problem in this study is: How is the condition of children recognizing numbers, the use of number card media, and the condition of children recognizing numbers through number cards in Early Childhood RA Nurul Ummi Binjai Baru, Batubara Regency. This research uses qualitative research by describing in the form of words and language, in a special natural context, and by utilizing various natural methods. The results of the research that the authors found were that: The condition of children recognizing numbers in RA Nurul Ummi Binjai Baru, Batubara Regency Knowing numbers has become mandatory, children consider numbers as a series of meaningless words and learning to recognize numbers is boring. Teachers must use interesting and fun methods and media in introducing the concept of numbers. The state of using number card media at RA Nurul Ummi Binjai Baru, Batubara Regency, is a number card or card props are tools or equipment used by a teacher in teaching in the form of cards with numbers written in accordance with the theme being taught. Card props are tools for children to remember lessons. Letter card props can make an impression on the heart so that children don't easily forget them. In line with the child's memory of the props, he is also reminded of the lesson delivered by the teacher. The younger the child, the more he needs visualization/concrete (needs more props) that he can touch, see, feel, and hear. The conclusions are: The condition of children recognizing numbers through the media of number cards in Early Childhood at RA Nurul Ummi Binjai Baru, Batubara Regency, efforts to improve children's abilities through the media of numbers with the use of number card media that are applied in PAUD are very suitable for playing with cards can improve the ability to recognize numbers and provide excellent results for the development of children's abilities.